Dual functions of 2D WS2 and MoS2–WS2 monolayers coupled with a Ag3PO4 photocatalyst. (25th August 2016) - Wei, Zeng-Xi; Huang, Wei-Qing; Xu, Liang; Hu, Wangyu; Peng, P; Huang, Gui-Fang
Abstract: The photocatalytic performance of semiconductors can be improved by coupling two-dimensional (2D) layered materials. Understanding the underlying mechanism of this phenomenon at the electronic level is important for the development of photocatalysts with a high efficiency. Here, we first present a theoretical elucidation of the dual functions of 2D layered material as a sensitizer and a co-catalyst by performing density functional theory calculations, taking WS2 and a lateral heterogeneous WS2 –MoS2 monolayer as examples to couple with a promising photocatalyst Ag3 PO4 . The band alignment of a staggered type-II is formed between Ag3 PO4 and the 2D monolayer with the latter possessing the higher electron affinity, resulting in the robust separation of photoexcited charge carriers between them, and indicating that the 2D monolayer is an effective sensitizer. Interestingly, the W (Mo) atoms, which are catalytically inert in the isolated 2D monolayer, turn into catalytic active sites, making the 2D monolayer a highly active co-catalyst in hybrids. A better photocatalytic performance in the coupled lateral heterogeneous WS2 –MoS2 monolayer and Ag3 PO4 can be expected. The calculated results can be rationalized by available experiments. These findings provide theoretical evidence supporting the experimental reports and may be used as a foundation for developing highly efficient 2D layered materials-based photocatalysts.